2021
DOI: 10.1111/tpj.15252
|View full text |Cite
|
Sign up to set email alerts
|

A Plasmopara viticola RXLR effector targets a chloroplast protein PsbP to inhibit ROS production in grapevine

Abstract: Pathogens secrete a large number of effectors that manipulate host processes to create an environment conducive to pathogen colonization. However, the underlying mechanisms by which Plasmopara viticola effectors manipulate host plant cells remain largely unclear. In this study, we reported that RXLR31154, a P. viticola RXLR effector, was highly expressed during the early stages of P. viticola infection. In our study, stable expression of RXLR31154 in grapevine (Vitis vinifera) and Nicotiana benthamiana promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 76 publications
0
29
0
Order By: Relevance
“…Evidence points to the potential for RXLR effectors to drive plant cell death following recognition by the corresponding R proteins or unknown mechanisms (Huang et al, 2019 ). Many of RXLR effectors have a second EER-motif (glutamic acid-glutamic acid-arginine optional amino acid motif) participating in the transport from the pathogen to its host, and at varying distance C-terminal to RXLR motif (Stassen and Van Den Ackerveken, 2011 ; Liu et al, 2021 ). Both RXLR and EER motifs are needed to access host cells (Kale and Tyler, 2011 ).…”
Section: Plasmopara Viticolamentioning
confidence: 99%
“…Evidence points to the potential for RXLR effectors to drive plant cell death following recognition by the corresponding R proteins or unknown mechanisms (Huang et al, 2019 ). Many of RXLR effectors have a second EER-motif (glutamic acid-glutamic acid-arginine optional amino acid motif) participating in the transport from the pathogen to its host, and at varying distance C-terminal to RXLR motif (Stassen and Van Den Ackerveken, 2011 ; Liu et al, 2021 ). Both RXLR and EER motifs are needed to access host cells (Kale and Tyler, 2011 ).…”
Section: Plasmopara Viticolamentioning
confidence: 99%
“…Different suborganelles in the host often become targets of pathogens [ 23 , 39 ]. Many effectors target different components of the PSII in the host, which interferes with electron transport and inhibits ROS production, interfering with plant defense [ 6 , 28 , 40 ]. The effector RXLR31154 of Plasmopara viticola targets PsbP (a factor of the oxygen-evolving complex of PSII) to inhibit H 2 O 2 production in a grapevine and enhance its susceptibility [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many effectors target different components of the PSII in the host, which interferes with electron transport and inhibits ROS production, interfering with plant defense [ 6 , 28 , 40 ]. The effector RXLR31154 of Plasmopara viticola targets PsbP (a factor of the oxygen-evolving complex of PSII) to inhibit H 2 O 2 production in a grapevine and enhance its susceptibility [ 6 ]. In our study, we found that the effector Sntf2 of C. gloeosporioides migrated into the host’s chloroplasts and interacted with Mdycf39.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations